1997
DOI: 10.1002/(sici)1097-0142(19970115)79:2<294::aid-cncr13>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Follicular dendritic cell sarcoma

Abstract: Follicular dendritic cell sarcoma exhibits distinctive histologic features that permit its presumptive recognition, but a firm diagnosis requires confirmation with special studies. Because it has a significant recurrent and metastatic potential (the latter risk having been previously underestimated), it should be viewed as an intermediate grade malignancy. An intraabdominal location is associated with a particularly aggressive clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
176
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(178 citation statements)
references
References 23 publications
1
176
1
Order By: Relevance
“…FDC sarcoma is a neoplasmatic proliferation of spindled to ovoid cells showing morphologic and immumophenotypic features of FDCs [5]. It is usually observed as lymphadenopathy, but it can also be present in a variety of extranodal sites and intra-abdominal organs, including the spleen [2].…”
Section: Discussionmentioning
confidence: 99%
“…FDC sarcoma is a neoplasmatic proliferation of spindled to ovoid cells showing morphologic and immumophenotypic features of FDCs [5]. It is usually observed as lymphadenopathy, but it can also be present in a variety of extranodal sites and intra-abdominal organs, including the spleen [2].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the follicular dendritic cells sometimes show dysplastic features (Figure 2B), and instances of follicular dendritic cell sarcoma have been described. 16, 17 In fact, recent molecular studies demonstrated clonality in the stromal cells in hyaline vascular Castleman disease, and suggested that genetic alteration in stromal cells including FDCs may be the underlying cause of the disease. 1820 …”
Section: Unicentric Castleman Diseasementioning
confidence: 99%
“…FDC sarcoma (FDCS), first described by Monda et al 3 in 1986, is a rare neoplastic proliferation showing morphological and immunophenotypic features of FDC. It can occur at nodal and extra-nodal sites, which were first described by Chan et al 4 5 in the oral cavity. Metastatic disease has also been observed in the lymph nodes, lung and liver 2.…”
Section: Introductionmentioning
confidence: 95%